Perlindungan Hukum terhadap Pekerja Usia Anak di Indonesia - Azali, Nur Azkiya; Zahratul Aini; Putri Anggun Sari; Ilham Hudi; M. Irfan Wahyudi; Chandra Halim (Katalis Pendidikan : Jurnal Ilmu Pendidikan dan Matematika, 2024)
The existence of child exploitation and child labor will add to labor problems in Indonesia. The term "child labor" refers to people who employ children. The term "child labor" can be associated with the use of children's labor with low compensation or considerations regarding their personality development, safety, health, and future prospects. Most child workers do not have time to play or go to school like other children. Underage people work as hard as adults, both in formal and informal jobs. To save child labor in the future, a holistic and comprehensive solution model is needed. One method that can be used is a client-centered case management approach (centered on the client or child worker).